Video Animasi tentang Pencegahan HIV/AIDS Mampu Meningkatkan Pengetahuan dan Sikap Remaja - Lutfi Ridwinnida Rahmatullah; Sutrisno Sutrisno; Suzanna Suzanna; Kgs. Muhammad Faizal (Malahayati Nursing Journal, 2025)
ABSTRACT Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) is a disease that attacks the body's immune system. HIV disease continues to develop and is still a household chore both in the world and in Indonesia. The development of adolescents who feel curious and try new things makes adolescents feel happy and free to the point of being out of control and encourages them to commit deviant actions such as smoking, drinking alcoholic beverages, unhealthy dating styles to free sex so that they are at risk of contracting HIV/AIDS infectious diseases. The number of HIV/AIDS sufferers in adolescence continues to increase, therefore special nursing interventions are needed in the aggregate of school-age children, a form of promotive and preventive efforts, one of which is health education through animated videos. It is known that the influence of animated videos on HIV/AIDS prevention on adolescents' knowledge and attitudes. The Pre-Experimental research method with the One Group Pretest Posttest design design was carried out for two sessions for three days at SMP Negeri 2 Palembang with a sample of 90 respondents obtained using the purposive sampling technique. There was a difference in the median value of knowledge and attitude before and after the intervention was given through an animated video with the results of the statistical test, namely the wilcoxon test, which obtained a p-value of 0.001. There is a significant influence on the improvement of adolescent knowledge and attitudes in educational interventions through animated videos on HIV/AIDS prevention Keywords: HIV/AIDS, Knowledge, Adolescents, Attitudes, Animated Videos  ABSTRAK                                   Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) merupakan penyakit yang menyerang sistem imunitas tubuh. Penyakit HIV ini terus berkembang dan masih menjadi pekerjaan rumah baik di dunia maupun di Indonesia. Perkembangan remaja yang merasa penasaran dan mencoba hal-hal baru membuat remaja merasa senang dan bebas sampai diluar kontrol dan mendorong mereka melakukan tindakan yang menyimpang seperti merokok, minum-minuman beralkohol, gaya berpacaran tidak sehat hingga seks bebas sehingga remaja berisiko terkena  penyakit menular HIV/AIDS. Penderita HIV/AIDS pada usia remaja terus bertambah oleh karena itu diperlukan intervensi keperawatan khusus pada agregat anak usia sekolah bentuk upaya promotif dan preventif salah satunya pendidikan kesehatan melalui video animasi. Diketahui pengaruh video animasi tentang pencegahan HIV/AIDS terhadap pengetahuan dan sikap remaja. Metode penelitian Pra Eksperimental dengan desain One Group Pretest Posttest design yang dilaksanakan selama dua sesi selama tiga hari di SMP Negeri 2 Palembang dengan sampel yang berjumlah 90 responden yang diperoleh menggunakan teknik purposive sampling. Ada perbedaan nilai median pengetahuan dan sikap sebelum dan sesudah diberikan intervensi melalui video animasi dengan hasil uji statistik yaitu wilcoxon test didapatkan nilai p-value 0,001. Adanya pengaruh signifikan pada peningkatan pengetahuan dan sikap remaja dalam intervensi edukasi melalui video animasi terhadap pencegahan HIV/AIDS. Kata Kunci: HIV/AIDS, Pengetahuan, Remaja, Sikap, Video Animasi